2018
DOI: 10.1029/2018jc014381
|View full text |Cite
|
Sign up to set email alerts
|

Wave Generation, Dissipation, and Disequilibrium in an Embayment With Complex Bathymetry

Abstract: Heterogeneous, sharply varying bathymetry is common in estuaries and embayments, and complex interactions between the bathymetry and wave processes fundamentally alter the distribution of wave energy. The mechanisms that control the generation and dissipation of wind waves in an embayment with heterogeneous, sharply varying bathymetry are evaluated with an observational and numerical study of the Delaware Estuary. Waves in the lower bay depend on both local wind forcing and remote wave forcing from offshore, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…In the present study, the tidally averaged significant wave height ( H s ) mirrors the broad basin topography with maximum values in the deepest regions of the lower bay ( H s ~ 1.5 m, Figure a) and reflects the findings by Chen et al () regarding equilibrium and disequilibrium conditions. Wave heights at shoreline edges in the lower bay were relatively small ( H s ~ 0.25 m), which is indicative of enhanced energy dissipation through bottom friction and whitecapping as waves propagate onshore.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In the present study, the tidally averaged significant wave height ( H s ) mirrors the broad basin topography with maximum values in the deepest regions of the lower bay ( H s ~ 1.5 m, Figure a) and reflects the findings by Chen et al () regarding equilibrium and disequilibrium conditions. Wave heights at shoreline edges in the lower bay were relatively small ( H s ~ 0.25 m), which is indicative of enhanced energy dissipation through bottom friction and whitecapping as waves propagate onshore.…”
Section: Resultssupporting
confidence: 90%
“…The study concluded that remotely generated waves cannot deeply propagate into the bay and therefore that waves are predominantly generated by local wind. The latter is in agreement with findings by Chen et al () who concluded that local winds constitute the main source of wave energy in much of the bay. However, these studies did not evaluate the role of waves in the momentum budget, surface stresses, and subtidal exchange.…”
Section: Study Region: Delaware Baysupporting
confidence: 93%
See 3 more Smart Citations